Mode III testing of structural adhesive joints at elevated loading rates. (March 2022) - Schrader, Peer; Marzi, Stephan
Abstract: The Out-of-plane loaded Double Cantilever Beam (ODCB) test has proven to be a well-suited test method for determining both energy release rate and cohesive law of adhesive layers in mode III under quasi-static conditions. As the rate-dependency of the fracture behaviour of adhesive layers in shear is still a topic of ongoing research, we aim to investigate, whether the ODCB test can be modified to be applicable at elevated loading rates. For this purpose, the experimental setup of the ODCB test was modified to allow testing at elevated loading rates. Tests were performed on an epoxy adhesive at outer loading rates over several orders of magnitude, ranging from quasi-static conditions up to the maximum possible test speed of the used servo-hydraulic test machine. The results of these experiments are discussed thoroughly to gain insight into the applicability of the ODCB test at moderate loading rates. Furthermore, the experimental challenges associated with an increase in loading rate are highlighted to identify limitations of the experimental setup that need to be addressed when transitioning to impact testing. Highlights: Mode III testing at crack opening velocities over four orders of magnitude. Energy release rate of the tested adhesive in shear is independent of loading rate. Shear strength of the tested adhesive increases with loading rate.